Influência dos períodos e posições de armazenamento de mudas sobre o diâmetro do pseudocaule, número de folhas e altura das plantas de bananeira (Musa acuminata Simmonds e Sheperd) cv "Nanicão" - Manica, Ivo; Simão , Salim; Reis Condé, Alcides (Revista Ceres, 2025)
The effect of time and storage position of banana planting material on the development of banana plants (Musa acuminata Simmonds and Sheperd cv. ‘Nanicao’) was studied in Piracicaba, São Paulo. None of the treatments significantly influenced leaf number, pseudostem diameter and plant heigh until 137 days after planting. Two hundred thirteen days after planting, the plants grown from material planted immediately, with no storage period, had attained the greatest heights and pseudostem diameters. They also showed greater precocity in production of sprouts.